Seismic assessment of reinforced concrete columns with short lap splices. Issue 3 (August 2021) - Opabola, Eyitayo A; Elwood, Kenneth J
Existing reinforced concrete (RC) columns with short splices in older-type frame structures are prone to either a shear or bond mechanism. Experimental results have shown that the force–displacement response of columns exhibiting these failure modes are different from flexure-critical columns and typically have lower deformation capacity. This article presents a failure mode-based approach for seismic assessment of RC columns with short splices. In this approach, first, the probable failure mode of the component is evaluated. Subsequently, based on the failure mode, the force–displacement response of the component can be predicted. In this article, recommendations are proposed for evaluating the probable failure mode, elastic rotation, drift at lateral failure, and drift at axial failure for columns with short splices experiencing shear, flexure, or bond failures.